Subcontracted Further Education in England: a case study of a private provider - Bourne, Darren (2019)
Further Education (FE) is under-researched and not well understood, but subcontracted FE is virtually invisible, despite being a significant part of the sector: subcontracting accounted for around £800m, or 8% of the national FE spend, in 2016/17. This study gives voice to managers inside a subcontracted private provider, a near-silent part of the turbulent FE sector.